2020
DOI: 10.37521/ejpps25202
|View full text |Cite
|
Sign up to set email alerts
|

Gender Influences Bacterial Contamination of Reusable Cleanroom Operators’ Garments following Wear

Abstract: Operators are the primary source of cleanroom contamination, with the majority of their detritus identified as skin squames and their associated microorganisms. To reduce contamination, operatives are required to wear a specific arrangement of specialist garments. However, bacteria can evade this clothing and tarnish outer surfaces whilst operators work, with adverse implication for cleanroom environment and product sterility. Gender plays a significant role in bacterial dispersion, with male rates being in ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 38 publications
(58 reference statements)
0
7
0
Order By: Relevance
“…Bacterial isolates were recovered during our study examining influence of gender on the surface contamination of clean room operators' garments following wear (32). During this investigation the surface of clean room operators' garments were tested within the exit area of the changing area, prior to garment removal and immediately following their period of working in the cleanroom environment.…”
Section: Bacterial Recoverymentioning
confidence: 99%
See 1 more Smart Citation
“…Bacterial isolates were recovered during our study examining influence of gender on the surface contamination of clean room operators' garments following wear (32). During this investigation the surface of clean room operators' garments were tested within the exit area of the changing area, prior to garment removal and immediately following their period of working in the cleanroom environment.…”
Section: Bacterial Recoverymentioning
confidence: 99%
“…These studies confirmed properly gowned operatives disperse approximately 17,000 particles (21), including 180 MCPs per minute into the cleanroom environment (20). The polyester fibres of reusable garments were found to offer a substratum for microbial adherence, survival and growth (28)(29)(30) and that garment surfaces are subject to bacterial contamination following wear (31,32). In turn, garments become a vector for microbial dissemination within a cleanroom either via indirect airborne transmission (33) or direct surface transfer (34,35).…”
Section: Introductionmentioning
confidence: 99%
“…The polyester fibres of reusable cleanroom garments provide a suitable substrate for microbial adherence and growth [15][16][17] , with skin commensal S. aureus viability maintained for up to 56 days following initial adherence [16] . Such bacteria from the skin microbiome penetrate through the cloth and contaminate the outer surface of cleanroom garments [6,18] . These clothing fibres in turn become vectors for microbial transmission [19] , compromising the sterile environment and potentially the product via airborne dissemination [20] or direct surface-to-surface transfer [7,21] .…”
Section: Bacterial Contamination Of Cleanroom Garmentsmentioning
confidence: 99%
“…Despite gloved hands reported as a transmission mode within the cleanroom environment [7,30] the efficacy of glove use with respect to the contamination of cleanroom garments during their donning has not previously been investigated. Those studies which have examined the contamination of cleanroom garments sought to do so either with respect to operator gender [18] or time spent working in the cleanroom facility [6] with no consideration of dressing regimes.…”
Section: Use Of Gloves To Prevent Microbial Contaminationmentioning
confidence: 99%
See 1 more Smart Citation